Kesalahan Siswa dalam Mengerjakan Soal Sistem Persamaan Linear Dua Variabel Berdasarkan Kriteria Watson - Stepania Junita Sari; Timbul Yuwono (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
This study aimed to describe the errors that student made in completing the Two Variable Linear Equation System based on Watson's criteria. This was a descriptive qualitative study involving 29 students consisted of of 12 high-skilled students, 5 medium-skilled students, and 12 low-skilled students in 8th grade at SMP PGRI 6 Malang. The data were obtained from the types of errors that student made using the Two Variable Linear Equation System question tests and the results of the interviews based on the Watson's criteria indicators. The question sets used in this study had been verified by mathematics education lecturers and mathematics teachers. The results of this study were: a) high-skilled students were 'less thorough' at work; (2) medium-skilled students were ‘using data incorrectly at the early stages'; while (3) low-skilled students ‘did not give answers' because they did not understand the concepts of the learning materials. The three types of errors frequently made by students were errors in determining the operation to be used (mhk), errors in determining the stages of solving the question problems (mtl), and errors in drawing conclusions from the final results (kh).